Model Pengembangan Kampung sebagai Desa Inovatif (Studi Kasus Kota Palembang) - Dedi Rianto Rahadi (President University, 2016)
The village is a village resident innovative society able to recognize and address as well as the use of advanced technology or new ways to tackle the problem and improve the economy by way of using existing technology around his environment independently. This study aims to develop a model village as a village innovative. The research object in Palembang and the research methods used by kualititif descriptive approach. The results showed an innovative rural development model is needed to approach the competitive advantage of each in every village in Palembang. Poverty is difficult to remove, but with the advantages of each mengedapankan each household expected by society to be independent. Innovative village in Palembang developed in villages with the highest poverty levels the District Seberang Ulu I model with the involvement of all relevant elements between the government, employers and society.